RETRACTED: Amino Acid Imbalance in Atherosclerosis - P.A., Karavay; L.I., Nefyodov; N.L., Karavay (International Journal of Nutrition, 2020)
This article has been retracted on 18 March 2021. VIEW THE RETRACTION NOTICE (https://doi.org/10.14302/issn.2379-7835.ijn-25-5865) A mini-review of literature data on the mechanisms of formation of the stock of free amino acids and their derivatives in atherosclerosis and methods for correcting metabolic imbalance.
Keywords: amino acids; derivatives; atherosclerosis